2015
DOI: 10.2298/pif1503137s
|View full text |Cite
|
Sign up to set email alerts
|

Field dodder - how to control it?

Abstract: SUMMARYBroad geographic distribution and spectrum of hosts make field dodder, Cuscuta campestris, one of the most widespread and most harmful pests among flowering parasitic plants. Field dodder may become a problem in vegetable nurseries (e.g. tomato, sweet pepper and cabbage) or in potato or some other crop grown in plastic greenhouses. However, the most devastating damage comes from field dodder outbreaks in newly-established perennial legume crops (alfalfa, clover, etc.), which are generally the preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…are also identified that they are effective in managing Cuscuta gronovii and Cuscuta pentagona [34]. Also conidia suspension of Colletotrichum gloeosporioides has provided selective control of C. chinensis and C. australis in soybeans [34]; [35].…”
Section: Biological Controlmentioning
confidence: 99%
“…are also identified that they are effective in managing Cuscuta gronovii and Cuscuta pentagona [34]. Also conidia suspension of Colletotrichum gloeosporioides has provided selective control of C. chinensis and C. australis in soybeans [34]; [35].…”
Section: Biological Controlmentioning
confidence: 99%
“…C. campestris is a stem holoparasitic plant, an extensive climber having filiform stems or vines with twining slender stems lacking true roots and leaves. It has a reduced or absent photosynthesis apparatus, therefore, its development and growth rely on autotropic host plants for at least carbohydrates [1][2][3]. After proper attachment to the host's vascular system (xylem and phloem) through the haustoria [2], the parasite functions as an active sink, redirecting solutes away from autotrophic sink tissues.…”
Section: Introductionmentioning
confidence: 99%
“…After proper attachment to the host's vascular system (xylem and phloem) through the haustoria [2], the parasite functions as an active sink, redirecting solutes away from autotrophic sink tissues. Due to this parasitism, C. campestris is considered to be among the most destructive agricultural weeds, significantly reducing the yield and quality of the crops' products [3][4][5][6]. It attacks many broad-leaf plants, the most sensitive of which include alfalfa, carrot, tomato, sugar beet, onion, potato and several ornamental plants [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le genre Cuscuta comprend environ 200 espèces de plantes sans racines et parasitant les tiges de certaines plantes (Saric-Krsmanovic et Vrbnicanin, 2015). Certaines publications plus récentes ont classé, Cuscuta dans sa propre famille appelée Cuscutaceae (Mishra, 2009).…”
unclassified